The effects of Korean hand acupressure on postoperative pain, nausea, vomiting, and retching after thyroidectomy: A randomized controlled study protocol - Sevgi Gür; Seher Deniz Öztekin; İlhan Öztekin; Orhan Yalçın (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The aim of this study is to determine the effect of Korean hand acupressure applied after thyroidectomy on postoperative pain, nausea, vomiting, and retching of number and severity. MATERIALS AND METHODS: The type of study is a randomized study with a post-test-control group. The protocol was prepared according to the SPIRIT (Standard Protocol Items: Recommendations for Interventional Trials) 2013 checklist. The CONSORT 2017 guideline was followed in reporting the protocol. The study was conducted with 42 patients (intervention/control group = 21) who underwent thyroidectomy in a hospital in Istanbul between February 2021 and June 2022, who met the inclusion criteria, and whose verbal and written informed consent was obtained. Korean hand acupressure was applied for 3 min using mung bean seeds 30 min before anesthesia was given to the patients in the intervention group. The application was continued every 2 h after the operation. The application was terminated at the eighth hour. The control group (patients) received routine post-operative treatment and care. Pain severity, nausea, vomiting, and retching number and severity, antiemetic use, and Rhodes nausea, vomiting, and retching index score at the end of the 24th hour were evaluated at the 2nd, 6th, and 24th hour postoperatively. Data analysis was done with the SPSS 25.0 program. CONCLUSION: For the patients in the intervention and control groups, it was found that the number and severity of nausea and vomiting were highest in the 6th hour after surgery. The application of Korean hand acupressure was an effective nursing intervention on the retching state (number/severity) that developed at the 6th hour after thyroidectomy and reduced the use of antiemetics.